Actions to detect fraud in financial statements - Kanapickienė, Rasa; Grundienė, Živilė (Buhalterinės apskaitos teorija ir praktika, 2014)
The information provided in financial statements should be neutral and reliable thus enabling the users of the financial statements to make financially legitimate decisions regarding the perspectives of the company’s development. Therefore the reference documents regulating the composition of financial statements determine that the distortion of the assets, income, costs or other data is strictly forbidden. Nevertheless, fraud in financial statements is a relatively frequent phenomenon in business practice. Hence, in order to detect frauds effectively it is essential to systematize the actions of fraud detection. The aim of the research is to explore the actions of detecting fraud in financial statements, systematize them and evaluate the possibilities of their application in practice. The paper divides the actions of detecting fraud in financial statements into methods and procedures. The methods of detecting fraud in financial statements are classified regarding two aspects: 1) consistency of fraud investigation and 2) applied methods of investigation. According to the consistency of the research, the following methods are distinguished: a) gathering of fraud evidence; b) analysis of fraud risk factors and c) a detailed investigation. To implement each of the methods appropriate procedures are selected. In order to gather the evidence on fraud, it is expedient to apply the following procedures: the use of external (complainant) systems (police reports), secret operations, senior management audit, gathering of unofficial information, application of legal recommendations, confession. While carrying out the analysis of fraud risk factors it is expedient to apply inquiry, monitoring, and analytical procedures. The procedures of fraud detection in the detailed investigation should be classified as audit proofs by distinguishing the variants of these procedures that are more typical of the monitoring institutions. Experts positively evaluated the possibilities to practically apply the analysed actions of detecting fraud in financial statements.